Qur’anic Environmental Education: Al-Maraghi and Fi Dhilal al-Qur’an as a Response to the Ecological Crisis - Ihya Ulumudin (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
The global ecological crisis, which includes climate change, pollution, and environmental degradation, requires an approach that is not only technology-based but also incorporates spiritual and moral values. The Qur'an, as the guide for Muslim life, offers ecological principles that can serve as a foundation for environmental education. This study aims to identify and analyze ecological principles in the Qur'an based on the interpretations of Al-Maraghi and Fi Dhilalil Qur'an, and to formulate an Islamic environmental education model that is relevant to the context of modern education. This research employs a qualitative method with a thematic interpretation analysis approach, encompassing a literature review of ecological verses in the Qur'an and interviews with Islamic education experts. The findings reveal that the concepts of khalifah (human stewardship on earth) and amanah (responsibility for the environment) are fundamental principles in Islamic environmental education. The proposed educational model includes the integration of Islamic ecological values into the curriculum, the implementation of nature-based projects, and the utilization of digital media to enhance ecological awareness rooted in Islamic spirituality. This study contributes to the development of an educational approach based on Islamic values to raise ecological awareness among Muslim communities. Keywords: education, Qur'anic interpretation, ecological awareness.